Feedback Behaviour of Farmers about Radio Listening, Television Viewing, Farm Magazine and Newspaper Reading in Jaipur Region of Rajasthan - Arvind Kumar Jhajharia , I M Khan, Santosh Jhajharia, (Indian Journal of Extension Education, 2022)
The present study was conducted in Jaipur region of Rajasthan, which had AIR station, Doordarshan Kendra and Registrar Office of farm magazines and newspapers. Out of the five districts in Jaipur region, two districts Jaipur and Jhunjhunu and panchayat samities were selected randomly by using simple random sampling. From the selected two districts, 6 panchayat samities were selected randomly by using simple random method. From the selected panchayat samities, 29 villages in proportion to size of the selected panchayat samities.And fromeach village, 10 per cent respondents in proportion to the size of the selected villages, hence a total of 302 respondents were selected for the study.An interview schedule was used.Majority of the radio-listening farmers (89.40 %) and television-viewing farmers (73.84 %), mostly approached the progressive farmers after getting farm information, whereas a majority of the farm magazine-reading farmers (91.21 %) and newspaper reading farmers (85.34%) approached their neighbors after gettingfarm information through farmmagazine and newspaper.Only 32.78 per cent radio listening farmers, 51.99 per cent TV-viewing farmers, 16.89 per cent farm magazine- reading farmers and 15.79 per cent newspaper reading farmers approached farm radio/ TV officials or editors of farm magazines and newspapers. About 31.76 per cent of farm magazine-reading farmers and 21.43 per cent of the newspaper -reading farmers had written letters in response to farmmagazine articles and newspaper news. Themain purpose of farm newspaper-reading farmers correspondence were for getting advice on their agricultural or animal husbandry problems, for information on farm credit or rural development articles, news and for sending suggestions for improvement of farm newspaper articles. Only 6.29 per cent of the radio-owning farmers, 9.93 per cent of the TV-owning farmers participated in the radio and TV programmes.About 30.41 per cent and 41.35 per cent of farm magazine and newspaper subscribers participated in the contests given in farm magazines and newspapers. Majority of the respondents were contacted through letters by the farm radio officials of AIR Jaipur (9.93 %), TV officials of Doordarshan Jaipur (6.62%), editors of farmmagazines (9.46%) and editors of newspapers (10.53%),whereas the respondents who were contacted through farm and home visits by farm radio and TV personnel of AIR, Jaipur and Doordarshan Kendra, Jaipur and farmmagazine and newspaper editors were 4.97 per cent, 6.29 per cent, 2.70 per cent and 4.14 per cent, respectively. Majority of radio listening farmers (79.14 %), 69.54 per cent of TV viewing farmers, 54.06 per cent of farm magazine-reading farmers and 61.66 per cent of newspaper-reading farmers had medium level of feedback behaviour status. The radio-listening farmers, TV-viewing farmers, farmmagazine-reading farmers and newspaper-reading farmers had a significant agreement with regard to their feed back behaviour.